Fabrication of Au-doped mesoporous TiO2 supported on g-C3N4 as an efficient light-assisted catalyst for oxidative desulfurization of model fuels with different sulfur content - Behzad Moeinifard; Alireza Najafi Chermahini (Journal of Materials Science: Materials in Engineering)
Abstract In the present study, the mesoporous TiO2 that was supported on graphitic carbon nitride (g-C3N4) was decorated with Au. The nanocomposite (Au-m-TiO2/g-C3N4) has been successfully synthesized by combining sono-chemical and EISA methods and was subsequently used in photocatalytic oxidative desulfurization of dibenzothiophene (DBT) in n-octane as a model fuel and under visible illumination. The Au-m-TiO2/g-C3N4 photocatalyst was characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), UV–Vis diffusive reflectance spectra (UV–Vis DRS), high-resolution transmission electron microscopy (HR-TEM), Fourier transform infrared spectra (FT-IR), and nitrogen adsorption measurements. The removal efficiency of DBT was 98.7% under the optimized reaction conditions and under visible-light irradiation (λ > 400 nm).